Magnetization switching of a metallic nanomagnet via current-induced surface spin-polarization of an underlying topological insulator - Roy, Urmimala; Dey, Rik; Pramanik, Tanmoy; Ghosh, Bahniman; Register, Leonard F.; Banerjee, Sanjay K. (Journal of applied physics, 2015)
We consider a thermally stable, metallic nanoscale ferromagnet (FM) subject to spin-polarized current injection and exchange coupling from the spin-helically locked surface states of a topological insulator (TI) to evaluate possible non-volatile memory applications. We consider parallel transport in the TI and the metallic FM, and focus on the efficiency of magnetization switching as a function of transport between the TI and the FM. Transport is modeled as diffusive in the TI beneath the FM, consistent with the mobility in the TI at room temperature, and in the FM, which essentially serves as a constant potential region albeit spin-dependent except in the low conductivity, diffusive limit. Thus, it can be captured by drift-diffusion simulation, which allows for ready interpretation of the results. We calculate switching time and energy consumed per write operation using self-consistent transport, spin-transfer-torque (STT), and magnetization dynamics calculations. Calculated switching energies and times compare favorably to conventional spin-torque memory schemes for substantial interlayer conductivity. Nevertheless, we find that shunting of current from the TI to a metallic nanomagnet can substantially limit efficiency. Exacerbating the problem, STT from the TI effectively increases the TI resistivity. We show that for optimum performance, the sheet resistivity of the FM layer should be comparable to or larger than that of the TI surface layer. Thus, the effective conductivity of the FM layer becomes a critical design consideration for TI-based non-volatile memory.